2022
DOI: 10.13057/biodiv/d230225
|View full text |Cite
|
Sign up to set email alerts
|

Effects of plant growth regulator from seaweed extracts on expression of genes regulating the oil and related metabolites productions in oil palm

Abstract: Abstract. Kresnawaty I, Santoso D,Hudiyono S. 2022. Effects of plant growth regulator from seaweed extracts on expression of genes regulating the oil and related metabolites productions in oil palm. Biodiversitas 23: 793-800. Plant growth regulators (PGRs) have been used in agricultural practicesto regulate various processes, such as germination, vegetative growth, reproduction, maturation, leaf senescence and post-harvest. Seaweed extract as natural PGRs source containsauxin, cytokines, and gibberellins. Alth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…also contains a boosting hormone growth that has been shown to increase plant growth and yield (Ali et al, 2021& Pradhan et al, 2022 and containing lots of minerals essential from the sea needed by plants as well. Our prior research found that seaweed extract contains some plant hormone such as auxin, gibberelic acid (GA) and cytokinine, and also some amino acids especially glutamic acid (Kresnawaty et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…also contains a boosting hormone growth that has been shown to increase plant growth and yield (Ali et al, 2021& Pradhan et al, 2022 and containing lots of minerals essential from the sea needed by plants as well. Our prior research found that seaweed extract contains some plant hormone such as auxin, gibberelic acid (GA) and cytokinine, and also some amino acids especially glutamic acid (Kresnawaty et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…also contains a boosting hormone growth that has been shown to increase plant growth and yield (Ali et al, 2021& Pradhan et al, 2022 and containing lots of minerals essential from the sea needed by plants as well. Our prior research found that seaweed extract contains some plant hormone such as auxin, gibberelic acid (GA) and cytokinine, and also some amino acids especially glutamic acid (Kresnawaty et al, 2023).…”
Section: Introductionmentioning
confidence: 99%